Artemisia annua L.- Vernonia amygdalina Del: A Potential Herbal Artemisinin Combination Treatment against Malaria - Cissy, Nambejja; Ogwang, Patrick Engeu; Berna, Onegi; Norbert, Anyama; Esther, Matu (British Journal of Pharmaceutical Research, 2016)
Aim of Study: The aim of the study was to determine the potential of Vernonia amygdalina - Artemisia annual combination as a possible herbal artemisinin combination treatment of malaria. Place and Duration of Study: Study was conducted at Natural Chemotherapeutics Research Institute, Ministry of Health, Kampala Uganda and at the Centre for Traditional Medicine and Drug Original Research Article Research, Kenya Medical Research Institute, Nairobi Kenya, from March 2013 to January 2014. Methodology: After authentication of the plants, mature healthy Artemisia annua and Vernonia amygdalina leaves were collected and shade dried over 2 weeks. The dry materials were then each separately extracted by maceration using Petroleum ether and methanol. The filtrates obtained were first concentrated by fanning and then oven dried at 50°C to constant weight of dry extract. Eight groups of Plasmodium berghei ANKA infected mice were treated once daily for 4 days from the day of inoculation as follows; group I, 200 mg/kg bwt of A. annua methanol extract; group II, 125 mg/kg of V. amygdalina methanol extract; group III, 200 mg/kg of A. annua pet ether extract; group IV, 125 mg/kg of V. amgydalina pet ether extract; group V, 125 mg/kg of V. amygdalina + 200 mg/kg of A. annua methanol extracts group; VI, 125 mg/kg of V. amygdalina + 200 mg/kg of A. annua pet ether extracts; group VII (positive control), 15 mg/kg of artemisinin+ 3mg/kg of naphthoquine and group VIII (negative control), 0.2 ml 10% Tween 80. Parasitaemia in each mice was determined by microscopy on day 5 while survival times were recorded over 30 day period. The means of percent parasitaemia and survival times for each treatment group were determined and differences tested for significances using One-way analysis of variance followed by Student's t-test at P=0.05 using STATA version 13.0 statistical program. Results: The petroleum ether extracts combination produced 100% parasite clearance by day 5 just like the Artemisinin-Napthoquine. The survival times for the herbal combination were however poor and significantly less i.e 10.67±1.09 days compared to more than 30.0 ± 0.0 days for the ACT, P=0.000. Conclusion: The V. amygdalina-A. annua petroleum ether extract combination shows promise for use as a herbal artemisinin combination against malaria however the survival times need improvement to match that of the ACT
Keywords: Artemisia annua; Vernonia amygadalina; Herbal-combination; Malaria.